Mussels and canopy-forming algae as ecosystem engineers: their contribution to community organization in the rocky sublittoral - Westerbom, Mats; Koivisto, Maria (Frontiers Media SA, 2022)
Understanding the influence of biogenic habitats on species assemblage structure and ecosystem productivity is crucial for successful conservation of natural systems. Brown algae, Fucus vesiculosus, and blue mussels, Mytilus trossulus, coexist on sheltered and moderately wave exposed shallow rocky reefs of the northern Baltic Proper. Here, they function as important biogenic structures for an abundant associated macroinvertebrate fauna. Despite their dominance and space sympatry, there is little understanding of how they differ in their role as provisioners of biodiversity in this system. While Fucus has been recognized as an important habitat provider for decades, the similar role of blue mussels has been seriously understudied in the northern Baltic Proper, leading to pressing knowledge gaps and an underestimation of their role for overall biodiversity. In this study, we compared macroinvertebrate species assemblages within 40 rocky reefs where Fucus and Mytilus co-occur in either intermixed or adjacent assemblages. We show that both habitats represent a species rich and abundant community that are comparable regarding diversity. However, abundance and biomass of the associated community is much higher in the Mytilus habitat in relation to the Fucus habitat, implying a far higher secondary production in the former habitat. Recognizing key habitats and understanding how they differ in their ability to support biodiversity and ecosystem productivity is necessary for predicting community responses to human pressures, including an altered climate, and for implementing efficient mitigation actions to minimize loss of biodiversity.
Keywords: biodiversity; biodiversiteetti; monimuotoisuus; sinisimpukka; rakkolevä; Baltic Sea; Itämeri; conservation; luonnon monimuotoisuus; facilitation; foundation species; community composition; Fucus; Mytilus